COMPARISON OF FINANCIAL DISTRESS ANALYSIS USING THE “Z” SCORE MODIFICATION, X-SCORE, G-SCORE AND S-SCORE MODELS TO ANALYZE THE ACCURACY OF THE BANKRUPTCY PREDICTION IN THE MINING INDUSTRY PERIOD OF 2016 – 2018 - Winarso, Eddy (International Journal of Psychosocial Rehabilitation, 2020)
Coal mining companies in Indonesia have a high business risk because most of the production is exported abroad, especially in China and India. The quality of coal in Indonesia is in the low category because it only produces 5,100 to 5,100 cal/gram. With fluctuations in world prices and unstable demand resulting in fluctuations in profits resulting in disrupted company performance, thus experiencing financial distress. In this study the researchers chose a coal mining company because of the number of companies listed in the stock exchange with 24 companies, and 4 of them did not announce their annual reports continuously, so that the companies studied were 20 companies from 2016 to 2018 company financial statement data, which were processed using the analysis model financial distress revealed by (1) Z "Altman Modification score, (2) X score from Zmijewski, (3) Model G score from Grover, and (4) S score from Grover to analyze the accuracy of bankruptcy predictions. The results show that (1) there are differences in the accuracy of bankruptcy prediction between the Modified Z-Score Altman Model and the Springate S-Score Model for coal mining companies listed on the Stock Exchange in the 2016-2018 period. (2) There is a difference in the accuracy of bankruptcy prediction between the Modified Z-Score Altman Model and the Zmijewski X-Score on coal mining companies listed on the Stock Exchange in the 2016-2018 period. (3) There is a difference in the accuracy of bankruptcy prediction between the Modified Z"-Score Altman Model and the Grover G-Score Model for coal mining companies listed on the Stock Exchange in the 2016-2018 period. (4) There is a difference in the accuracy of bankruptcy prediction between the Springate S-Score Model and the Zmijewski X-Score in the coal mining companies listed on the Stock Exchange in the 2016-2018 period. (5) There is a difference in the accuracy of bankruptcy prediction between the S-Score Springate Model and the Grover G-Score Model in coal mining companies listed on the Stock Exchange in the 2016-2018 period. (6) There is a difference in the accuracy of bankruptcy prediction between Zmijewski’s X-Score model and Grover’s GScore model in coal mining companies listed on the Stock Exchange in the 2016-2018 period.